2011
DOI: 10.1021/ja207315h
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Substitution Reactions of Metallabenzynes

Abstract: The electrophilic substitution reactions of metallabenzynes Os(≡CC(R)═C(CH(3))C(R)═CH)Cl(2)(PPh(3))(2) (R = SiMe(3), H) were studied. These metallabenzynes react with electrophilic reagents, including Br(2), NO(2)BF(4), NOBF(4), HCl/H(2)O(2), and AlCl(3)/H(2)O(2) to afford the corresponding bromination, nitration, nitrosation, and chlorination products. The reactions usually occur at the C2 and C4 positions of the metallacycle. These observations support the notion that metallabenzynes exhibit aromatic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 98 publications
2
34
0
1
Order By: Relevance
“…Although examples of these compounds are still relatively rare as well, the large possible number of variationsi nr ing size, heteroatom choice, degree of saturation and substitution (as well as possible isomers) suggests this could potentially developi nto av ery large set of compounds. Compounds in this class that have already been reported [117] include metallabenzothiirenes, [37,46,78] metallabenzoxirenes, [59,129] metallabenzazirines [59] metallabenzofurans, [91,[130][131][132][133][134] metallabenzothiophenes, [73,135] metallabenzothiazole, [52] metallabenzothiazolium, [78] and metallabenzoxathioles. [59,117] Formation of the ruthenabenzothiophene dimer 24,( am etalla-analogue of benzo[b]thiophene) was recently reportedt o occur via CÀHa ctivation of the thiophenes ubstituent of ac oordinated vinyl carbene ligand.…”
Section: Fused-ring Metallabenzenesmentioning
confidence: 99%
“…Although examples of these compounds are still relatively rare as well, the large possible number of variationsi nr ing size, heteroatom choice, degree of saturation and substitution (as well as possible isomers) suggests this could potentially developi nto av ery large set of compounds. Compounds in this class that have already been reported [117] include metallabenzothiirenes, [37,46,78] metallabenzoxirenes, [59,129] metallabenzazirines [59] metallabenzofurans, [91,[130][131][132][133][134] metallabenzothiophenes, [73,135] metallabenzothiazole, [52] metallabenzothiazolium, [78] and metallabenzoxathioles. [59,117] Formation of the ruthenabenzothiophene dimer 24,( am etalla-analogue of benzo[b]thiophene) was recently reportedt o occur via CÀHa ctivation of the thiophenes ubstituent of ac oordinated vinyl carbene ligand.…”
Section: Fused-ring Metallabenzenesmentioning
confidence: 99%
“…We have demonstrated that a similar cyclic h 2 -allene complex, 2 ]Cl 2 , could isomerize to metallabenzene when CHCl 3 was employed as solvent in the reaction. [10c] By contrast, complex 4 is very stable in CHCl 3 under refluxing condition.…”
Section: Interconversion Of Metallabenzenes and Cyclic H 2 -Allene-comentioning
confidence: 99%
“…[1] Several approaches have been developed to construct a remarkable number of stable metallabenzene rings. [2] Common strategies previously employed are the formation of metallabenzenes from various unsaturated metallacycles, including four-, [3] five-, [4] and sixmembered metallacycles. [5] Reactivity studies of metallabenzenes demonstrated that the converse transformation could also be feasible.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, benzyne ( II′ )11, 12 and isobenzene ( III′ )13 are too reactive and short‐lived to be isolated. Among the reactions of metallabenzynes,9eh the interconversion of metallabenzyne and metallabenzene is particularly interesting9g, 14 because it resembles the mutual transformation of benzyne and benzene. On the other hand, isometallabenzenes remain rare,10 thus restricting the in‐depth studies of their chemistry.…”
Section: Introductionmentioning
confidence: 99%